Comportamento do cimento supersulfatado (CSS) sujeito à carbonatação natural - Brustolin, Adrieli (2023)
Due to the high consumption of cement today, the cement industry has made efforts to reduce environmental impacts, because Portland cement is made of natural materials and emits carbon dioxide (CO2) in its production. Thus, supersulfate cement (SSC) is an alternative type of cement, composed of 70-90% granular blast furnace slag, 10-20% calcium sulfate and a maximum of 5% alkaline activator. CSS uses industrial waste in its composition, has low energy expenditure and reduces CO2 emissions to the atmosphere. However, in addition to these advantages, the binder must have durability necessary for the cementitious matrix, ensuring that the physical and chemical properties remain for a prolonged time. In this regard, the occurrence of carbonation in reinforced concrete structures can cause despassivation of the reinforcements and loss of mechanical strength due to the attack of CO2 to the hydrated phases of the cement. Thus, this work aims to compare the behavior of SSC with CP IV in exposure to natural carbonation. For this, two SSC formulations were investigated by compressive strength test, void indexes, carbonation depth measurements and microstructure analysis by means of X-ray diffractometry (XRD) and thermogravimetry (TG/DTG). The mechanical tests over the exposure period confirmed the loss of mechanical resistance due to the decomposition of hydration products responsible for the cementitious matrix's resistance gain (etringite and C-S-H), demonstrated in the microstructures analysis. The carbonation depth measurement results of both SSC formulations reached more than 5 mm after 28 weeks of exposure, and the CP IV trace did not obtain any measurements. It was possible to observe that the SSCs developed in this work have low carbonation resistance, because it reaches great depth quickly and significantly loses its compressive strength that is essential in concrete structures.